Applying artificial intelligence for the application of bridges deterioration detection system - Xuan-Kien Dang; Le Anh-Hoang Ho; Xuan-Phuong Nguyen; Ba-Linh Mai (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
Recently, advances in sensor technologies, data communication paradigms, and data processing algorithms all affect the feasibilities of the bridges structural health monitoring and deterioration detection, and other implementations of monitoring operations. The paper proposes a method to design an irregularity detection and monitoring system for road bridges that combines internet of things (IoT) and artificial intelligence (AI) technologies. Raspberry Pi 4 embedded computer integrating IoT and AI technology with convolutional neural network (CNN) is employed to simultaneously monitor remote bridges on websites and apps via Google Firebase cloud database. The first step of successful testing in the laboratory showed that the system can work stably and coincide with the proposed goals.